Le palmier à huile : un avenir pour l’Amazonie ? - Martine Droulers; Adriano Venturieri; Moises Mourão; Marcelo Thalês; René Poccard (Confins)
The production of palm oil, which represents an interesting alternative for decentralized production and use of biodiesel, would also an appropriate solution for the recovery of degraded areas in Amazonia, especially south of Belem? The heart of the demonstration is here rather the territorial impact of plantations and on the territorialities that are being implemented with the installation of this production in the Guajarina region